Approaching the advance of the agricultural border as presented by two High School textbooks (Huellas, 2016)
This paper aims at analyzing and comparing two textbooks designed for the third year of High School as regards the way in which they approach the agricultural border advance in Argentina. Both textbooks express the points of view of academic writers, mainly from the field of Geography but also from other Social Sciences as well. Our purpose is to analyze whether the relationship between the type of knowledge proposed by the curriculum of the province of La Pampa and the proposals introduced by the textbooks through the authors’ perspectives is made evident. Departing from this premise, then, we can introduce the following question: Will it be possible to teach and learn this topic from different perspectives and approaches based on the tenets of Social and Critical Geography, taking into account what the National Law of Education (LEN) prescribes? In reference to the proposed aim it will be of crucial importance to promote a comprehensive approach which might lead to a better understanding of the territorial logic of the social subjects. This will in turn lead to understand the different points of view and the multiple dimensions: economic-productive, political, socio-demographic, cultural and environmental which play different roles in the process of soybean production in Argentina’s rural areas, known in Spanish as “sojización.”
Keywords: geography – teaching – advance of the agricultural border – text-books proposals